2016
DOI: 10.1007/s11856-016-1321-x
|View full text |Cite
|
Sign up to set email alerts
|

The classification of homotopy classes of bounded curvature paths

Abstract: Abstract. A bounded curvature path is a continuously differentiable piecewise C 2 path with a bounded absolute curvature that connects two points in the tangent bundle of a surface. In this work, we analyze the homotopy classes of bounded curvature paths for points in the tangent bundle of the Euclidean plane. We show the existence of connected components of bounded curvature paths that do not correspond to those under (regular) homotopies obtaining the first results in the theory outside optimality. An applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…We use an idea similar and inspired by Birkhoff curve shortening (see [10]). Similar ideas and related studies by others may be found in [18], [9], [8], [5], [6] and [7]. Given a curve γ ∈L ρ 0 (Q), let L 0 be the length of γ, we construct a new curve that is shorter than or has the same length as the original curve, by the following process: we separate the curve in small sections, each section, except the first and last (that have length ≤ l), have the fixed length l, with l ≤ π sin ρ 0 .…”
Section: Curve Shorteningsupporting
confidence: 89%
See 4 more Smart Citations
“…We use an idea similar and inspired by Birkhoff curve shortening (see [10]). Similar ideas and related studies by others may be found in [18], [9], [8], [5], [6] and [7]. Given a curve γ ∈L ρ 0 (Q), let L 0 be the length of γ, we construct a new curve that is shorter than or has the same length as the original curve, by the following process: we separate the curve in small sections, each section, except the first and last (that have length ≤ l), have the fixed length l, with l ≤ π sin ρ 0 .…”
Section: Curve Shorteningsupporting
confidence: 89%
“…From Theorem 3.2 and Proposition 3.7 for ρ =ρ, P = Q i and Q = Q i+1 , the length-minimizing curve is of type CSC. The continuity can be proven by using the same argument as J. Ayala and H. Rubinstein's argument in [8] for the plane case. The idea is to define a region Ω that depends continuously on Q i and Q i+1 .…”
Section: Definition Of the First Part Of Fmentioning
confidence: 85%
See 3 more Smart Citations